STRATEGI MANAJEMEN MARKETING MADRASAH ALIYAH NEGERI (MAN) KLATEN TAHUN 2016/2017 - Hidayat, Hanifan Hani (El-Hayah, 2018)
Abstract : This research is conducted to obtain information about the marketing strategy at Madrasah Aliyah Negeri (MAN) Klaten in 2016/2017. It is undeniable that today madrassas (Islamic schools) are still considered as second caste school after public school. However, the public interest always increases for MAN Klaten every year. This study aims at describing strategies of marketing management, supporting and inhibiting factors and solutions of marketing management strategy of Madrasah Aliyah Negeri Klaten.This research used qualitative descriptive. This research was conducted at MAN Klaten from November to June 2017. Subject of this study was Vice of Student Affair. Informants were Principal, Vice of Public Relation. Sources of data were observation, interview and documentation. Technique of data validity used source and method triangulation. Data analysis techniques applied interactive analysis money including data collection, data presentation, data reduction, and conclusion.The results of the research reveal the implementation of marketing management strategy at Madrasah Aliyah Negeri (MAN) Klaten in 2016/2017, can be described by determining: (1) Before implementing marketing strategy, it has been set the steps by forming a promotion team named socialization team, (2) direct marketing by sending promotion teams named socialization teams to come to schools to introduce the products offered, (3) indirectly marketing is doneÂ  through: sending delegates in events or competitions, such as marching band, scout, art competition (hadrah and band), and sports field (baket ball, futsal, pencak silat, sacred tread, etc. ), conducting try out for Junior High schoolâ€™s students, banners / brochures and online media, (4) the public interest has been created from students studying at MAN Klaten, (5) supporting factors are: Human Resources designated as socialization team is appropriate and able to market MAN Klaten, and fund to create brochures / banners has already budgeted from BOS funds, (6) inhibiting factors are when direct socialization to schools requires transportation, whereas transportation at MAN Klaten is only one and often used by the Principal.Keywords: Marketing Strategy and Management